Investigation of highly sensitive surface plasmon resonance biosensors with Au nanoparticles embedded dielectric film using rigorous coupled wave analysis - Wu, Bin; Wang, Qing-Kang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The detection performance of conventional surface plasmon resonance (SPR) biosensors is limited by its own mechanism. Recently, novel highly sensitive SPR biosensors with Au nanoparticles enhancement are proposed to detect the interaction of small molecules in low concentrations. In this study, the effect of Au nanoparticles enhancement is firstly calculated by using the Maxwell–Garnett effective medium theory (EMT). Then, the influence of different structural parameters of nanoparticles embedded film on the performance is thoroughly investigated by the rigorous coupled wave analysis (RCWA). Electric field distributions in the nanoparticles embedded film are also given. The results strongly indicate that the sensitivity improvement can be achieved by adding a nanoparticle embedded film with optimal structural parameters. The simulation method of RCWA is also proved to be a powerful tool to optimize nanoparticles embedded film based biosensor.
Optica Applicata, Vol. 39, 2009, nr 1, s. 31-41
Keywords: optyka; surface plasmon resonance biosensor; nanoparticles enhancement; effective medium theory (EMT); rigorous coupled wave analysis (RCWA)